AB0526 Patient Characteristics, Treatment Patterns, Resource Utilization and Costs of Sjogren's Syndrome Using A U.S. Managed Care Prescription Claims Database. (9th June 2015) - Birt, J.; Tan, Y.; Lin, C.-Y.; Wang, Y.; Mozaffarian, N.
Abstract : Background: Sjogren's syndrome (SS) is a systemic autoimmune disease associated with lymphocytic infiltration of the exocrine glands, often accompanied by widespread pain and fatigue. There is no approved disease-modifying agent for SS and little information on SS treatment practices [1]. Objectives: To better understand the patient population and real-world standard of care for SS, we conducted a retrospective study using the MarketScan Commercial Claims database. Methods: We identified 11, 385 patients ≥18 years old with ≥1 inpatient or ≥2 outpatient SS diagnosis codes (ICD-9-CM code: 710.2) from Jan. 1, 2006 to Dec. 31, 2011. Patients with continuous pharmaceutical/medical benefits for 12 months pre- and post-index were selected to obtain patient characteristics, drug and resource utilization, and medical costs. Results: 90% of patients were female (mean age 55 years); physician specialties associated with initial SS diagnosis were rheumatology (39.0%), internal medicine (14.2%), family practice/medical doctor (13.9%), and ophthalmology (6.1%). Common comorbidities among SS patients were: hypertension (37.1%), osteoarthritis (30.9%), hyperlipidemia (29.6%), and mental disorders (25.0%). Approximately 54% of patients had another autoimmune condition; most commonly: rheumatoid arthritis (17.5%), systemic lupus erythematosus (14.5%), and unspecified inflammatory polyarthropathy (6.4%). Anti-rheumatic medications prescribed during the 12 months post-diagnosis were: low dose steroid ([<20mg/d prednisone equivalent], 21.3%), hydroxychloroquine (21.0%), topical cyclosporine (15.0%), and cevimeline (14.9%). Approximately 6.1% of patients were on a biologic, 37.3% were on a synthetic immunomodulator, and 7.1% were on high dose steroids (≥20mg/d prednisone equivalent). In patients without concurrent autoimmune diagnoses 0.3% were on a biologic, 19.3% were on a synthetic immunomodulator, and 5.5% were on high dose steroids. Of note, 15.1% of patients received no anti-rheumatic medications. In the 12 months post-SS diagnosis, total medical resource utilization was 1.2 times higher and total medical costs were 1.4 higher, compared to pre-diagnosis. Conclusions: This retrospective analysis of a large group of real-world SS patients provides important insights into treatment practices and medical resource utilization. More than half of the patients with SS were diagnosed by a non-rheumatologist. Compared to pre-diagnosis, greater health care costs were incurred after SS diagnosis. Pharmacologic management of SS consisted primarily of low-grade immunomodulation and symptomatic treatments. Systemic disease-modifying therapies were used in a minority of SS patients and most of these patients had other autoimmune diagnoses, suggesting there may be a large unmet need in patients with SS. References: Brito-Zeron P, et al. Primary Sjogren Syndrome: an update on current pharmacotherapy options and future directions. Exp Opin on Pharmacother 2013;14(3):279-89. Disclosure of Interest: J. Birt Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, Y. Tan Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, C.-Y. Lin Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, Y. Wang Shareholder of: Inventiv Health, Employee of: Inventiv Health, N. Mozaffarian Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company